Solidification and crystallization processing in metals and alloys - Fredriksson, Hasse; Akerlind, Ulla (John Wiley & Sons, Ltd, 2012)
Coauthored by an authority on solidification and developed from lecture notes from courses taught at KTH over the last 30 years, this guide shows the link between theory and experimental results, and gives the theoretical background to common solidification problems.